To Engage or Not Engage? Looking at the Barriers Behind Low Retention Rates of Racial/Ethnic Online Adult Learners - Saundra Pearl Peterson; Geleana Drew Alston (Adult Education Research Conference, 2015)
Distance education leadership must be central to influencing organizational change due to the societal needs for educated adults that can contribute and thrive in a complex, technologically driven, pluralistic, team oriented global workforce society. This roundtable will examine the relationship between distance learning leadership and culturally relevant educational experiences in order to understand how leadership effectiveness and organizational change can be innovative in improving persistence of racial/ethnic adult online learners.
Keywords: adult education online; attrition rates and online racial/ethnic adult learners; adult learners and culturally relevant online education; distance education leadership and culturally relevant online learning environment